Rifampicin-monoresistant Mycobacterium tuberculosis among the patients visiting chest clinic, state specialist hospital, Akure, Nigeria - Bello, Lateef A.; Shittu, Mujeeb O.; Shittu, Bashirat T.; Oluremi, Adeolu S.; Akinnuroju, Oluwagbenga N.; Adekola, Saheed A. (International Journal of Research in Medical Sciences, 2017)
Background:Tuberculosis (TB), one of the most important contagious diseases, is a leading cause of death due to a single pathogen worldwide. Co-infection of people living with HIV with M. tuberculosis has been shown to increase the mortality rate in sub-Saharan Africa. Methods:This present study was carried out to establish the rifampicin resistant profiles among the patients attending chest clinic, state specialist hospital, Akure. We enrolled clinical samples submitted between January 2013 and December 2013 for this study. The sputum samples were analyzed using GeneXpert. Results:Of the 135 sputum processed by GeneXpert, 48 (35.6%) contained Mycobacteria tuberculosis (MTB) and 9 (18.8%) were rifampicin resistant Mycobacteria tuberculosis. Patients within the age group of 24-32 years showed the highest resistant to RIF 6 (12.5%). Conclusion:This study has helped to establish that there is presence of rifampicin resistant Mycobacterium tuberculosis in Akure, Ondo state, Nigeria and most of them were observed among patients who default treatment. This is considered as a threat to TB control programme in Akure, Nigeria and it is recommended that strategies should be put in place in order to ensure patients’ compliance and monitoring of patients’ response to TB treatment.